Optimal codomains for the Laplace operator and the product Laplace operator - Josefina Alvarez; Lloyd Edgar S. Moyo (Journal of Function Spaces and Applications, 2007)
An optimal codomain for an operator P (∂) with fundamental solution E, is a maximal space of distributions T for which it is possible to define the convolution E*T and thus to solve the equation P (∂)S=T. We identify optimal codomains for the Laplace operator in the Euclidean case and for the product Laplace operator in the product domain case. The convolution is understood in the sense of the S′-convolution.